2018
DOI: 10.1186/s40249-018-0460-1
|View full text |Cite
|
Sign up to set email alerts
|

Climate drivers of vector-borne diseases in Africa and their relevance to control programmes

Abstract: BackgroundClimate-based disease forecasting has been proposed as a potential tool in climate change adaptation for the health sector. Here we explore the relevance of climate data, drivers and predictions for vector-borne disease control efforts in Africa.MethodsUsing data from a number of sources we explore rainfall and temperature across the African continent, from seasonality to variability at annual, multi-decadal and timescales consistent with climate change. We give particular attention to three regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
0
46
1
Order By: Relevance
“…Environmentally-informed disease risk monitoring and prediction has proven to be useful for numerous infectious diseases 6 , including viral upper respiratory infections 7 like COVID-19. These disease risk forecasts have been applied to vaccination strategies 8 and have demonstrated value for informing deployment of non-pharmaceutical preventative measures and treatments 9,10 .…”
mentioning
confidence: 99%
“…Environmentally-informed disease risk monitoring and prediction has proven to be useful for numerous infectious diseases 6 , including viral upper respiratory infections 7 like COVID-19. These disease risk forecasts have been applied to vaccination strategies 8 and have demonstrated value for informing deployment of non-pharmaceutical preventative measures and treatments 9,10 .…”
mentioning
confidence: 99%
“…Vector‐borne diseases account for approximately 17% of all infectious diseases and continue to be a significant public health problem, particularly in Africa, where the climate is highly favorable for the transmission of these pathogens . Long‐term trends in warming are predicted to have the greatest negative impact in the highland regions of Eastern and Southern Africa, where moderate temperatures have thus far been relatively unfavorable for tropical pathogens and their vectors …”
Section: Climate Change and Infectious Diseasesmentioning
confidence: 99%
“…Previous research 8,11,16 has underscored the importance of analyzing climate signals at multiple timescales to improve decision-making processes in the health sector. In particular, Muñoz et al 16 and Thomson et al 11 have shown that the seasonal-to-interannual timescale tends to explain most of the total variance observed in climate variables impacting vector-borne disease transmission, like temperature and rainfall.…”
Section: Aedes Uncertainties and Decision-makingmentioning
confidence: 99%
“…Nonetheless, there is increasing interest in using models for real-time forecasting and climate-and-health services 7 9 , with still important gaps in the operational readiness of several forecasting systems proposed in the literature 10 . Stochastic models are frequently used in climate and disease modeling to build probabilistic forecasts 11 , as they provide a more reliable assessment of the range of likely outcomes. However, probabilistic models are sometimes harder for decision makers to interpret, and tend to be rejected in favour of simpler, deterministic, but over-confident, models.…”
Section: Introductionmentioning
confidence: 99%